2012
DOI: 10.15376/biores.8.1.472-486
|View full text |Cite
|
Sign up to set email alerts
|

The Elongation Potential of Paper – How Should Fibres be Deformed to Make Paper Extensible?

Abstract: aElongation at failure is an important but underrated functional property of paper. Traditionally, elongation has been of specific importance for sack and bag paper grades. Mechanical treatments at high consistency are known to induce fibre deformations that contribute to the elongation of paper. However, it is not clear to what extent different fibre deformations can improve the elongation of paper. The aim of this work was to investigate the influence of three mechanical treatments on fibre and paper propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 8 publications
1
31
1
Order By: Relevance
“…However, in earlier microscopy research (Joutsimo 2004), fiber surface fibrillation analysis was not able to detect differences in the fibrillation of treated and untreated fibers. Also, Zeng et al (2013) reported similar results to ours; after treating bleached pulp mechanically at 170 o C, the pulp sheet density decreased from ~510 to ~470 kg/m 3 while fines content increased from ~6 to ~9%.…”
Section: Cooking Hemicellulose Composition and Pulp Sheet Densitysupporting
confidence: 88%
“…However, in earlier microscopy research (Joutsimo 2004), fiber surface fibrillation analysis was not able to detect differences in the fibrillation of treated and untreated fibers. Also, Zeng et al (2013) reported similar results to ours; after treating bleached pulp mechanically at 170 o C, the pulp sheet density decreased from ~510 to ~470 kg/m 3 while fines content increased from ~6 to ~9%.…”
Section: Cooking Hemicellulose Composition and Pulp Sheet Densitysupporting
confidence: 88%
“…This relationship is well known (Vainio and Paulapuro 2007), but no models have been proposed. It is also well known that increasing the paper density strongly improves the paper strength (Santos et al 2006;Anjos et al 2011;Santos et al 2012;Zeng et al 2013), which is mostly due to increased fiber-fiber contact. There is a strong inverse relationship between the density and the light scattering coefficient (Batchelor and He 2005;Hubbe et al 2008).…”
Section: Multivariable Regression Modelsmentioning
confidence: 98%
“…Steenberg (1949) noted that paper formed from fibers that are "creased" so that they include a bend between adjacent crossing points with other fibers, can be expected to withstand a greater degree of shock. Thus, when papermakers set out to make tough bags to hold cement and similar products, the processing conditions are optimized to maximize the extensibility of the paper (Edwards and Edmunds 1968;Vishtal and Retulainen 2012;Zeng et al 2013). Such products are typically prepared with a minimum of tension applied during drying, thus allowing the paper structure to shrink and giving it more potential to be later stretched without breakage.…”
Section: Fiber Straightnessmentioning
confidence: 99%